The practical implications of taxing the informal sector in Zimbabwe - Mashate, Fredy (Rhodes University, Faculty of Commerce, Department of Accounting)
The taxation of informal sector business is increasingly becoming a topical issue in many developing countries, and Zimbabwe is no exception. The Zimbabwean government has been experiencing shrinking revenue in the wake of an increased informal sector and a declining formal sector. In an effort to broaden the tax base and increase revenue for government in Zimbabwe, presumptive tax levied against certain informal sector activities was first introduced in 2005 and later expanded to other sectors. Despite the effort, the informal sector has responded with low tax morale and non-compliance, which creates the need to reassess the current administrative strategies in a bid to build a successful tax system for the informal sector. The main goal of the research is to establish clear, innovative and practical administrative strategies that can be adopted by the Zimbabwe Revenue Authority in taxing the informal sector in Zimbabwe. An initial investigation was done to identify the current state of affairs in relation to informal sector taxation in Zimbabwe. A number of challenges were recorded and the research the sought to learn from examples of recent innovation in administrative strategies successfully applied in taxing the informal sector in other jurisdictions like Tanzania and Ghana. Learning from these examples, a number of practical administrative strategies that are mindful of the Zimbabwean economic context were proposed.
Keywords: Informal sector (Economics) -- Taxation -- Zimbabwe; Small business -- Taxation -- Law and legislation -- Zimbabwe; Tax administration and procedure -- Zimbabwe; Taxpayer compliance -- Zimbabwe; Taxation -- Public opinion; Zimbabwe Revenue Authority; Informal sector (Economics) -- Taxation -- Tanzania; Informal sector (Economics) -- Taxation -- Ghana